Faktor Yang Berhubungan Dengan Kejadian Pneumonia Pada Balita Di Rumah Sakit TK II Pelamonia Makassar - Dwi Yuliana Citra; Andi Nurlinda; Mansur Sididi (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2026)
Pneumonia is an acute respiratory infection that attacks the lungs. The lungs consist of small sacs called alveoli, which fill with air when a healthy person breathes. This study aims to determine the factors associated with pneumonia incidence among toddlers at the Makassar Class II Pneumonia Hospital. The research design is quantitative and cross-sectional. The study population consisted of 96 respondents. The sample calculation used the Lemešow formula, yielding a sample of 77 respondents. The instrument used was a questionnaire. Data analysis used univariate and bivariate analysis. The analyzed data are presented in tabular form, followed by a narrative explanation. The results of the study showed that there was a relationship between nutritional status and the incidence of pneumonia in toddlers, namely (p = 0.000 <0.05), there was a relationship between LBW and the incidence of pneumonia in toddlers, namely (p = 0.004 <0.05), there was no relationship between immunization status and the incidence of pneumonia in toddlers, namely (p = 0.083 <0.05), there was a relationship between exclusive breastfeeding and the incidence of pneumonia in toddlers, namely (p = 0.040 <0.05), there was a relationship between the provision of vitamin A and the incidence of pneumonia in toddlers, namely (p = 0.007 <0.05), there was a relationship between smoking behavior of family members and the incidence of pneumonia in toddlers, namely (p = 0.036 <0.05), there was a relationship between the use of mosquito repellent and the incidence of pneumonia in toddlers, namely (p = 0.028 <0.05). It is hoped that parents/caregivers of toddlers will pay more attention to the risk factors for pneumonia.